Considerations for single tooth replacement in an esthetic zone-review of conservative treatment options - Raghuwar Dayal Singh; Saumyendra V Singh; Pooran Chand; Ramashanker (Elsevier, 2011)
ABSTRACT: Background: This literature review aimed to identify and assess the conservative treatment options for replacing a single missing anterior tooth, for patients who cannot afford implants or traditional bridges. Materials and Methods: The evidence was obtained using MEDLINE searches. A total of 19 studies met the inclusion criteria. None of these studies scored higher than 10 of 17, suggesting that all studies did not have strong evidence. Three of the studies examined resin-bonded bridges (RBBs), whereas the other three investigated removable partial dentures (RPDs). None of the studies had random patient selection. Three of these studies had controlled allocation of patients. The other three allowed new patients to enter the study throughout the study period. Placement of the prosthesis was only conducted in one study, whereas the rest of the studies examined patients with preexisting prostheses. Results and Conclusion: In general, all 19 studies were weak due to poor study design, no acceptable controls, no direct comparison between RBBs and RPDs, lack of longitudinal studies and no differentiation between the anterior and posterior prostheses. Therefore, no definitive treatment conclusion can be made until studies of stronger design are conducted.